SURGICAL TACTICS IN COMBINED GYNECOLOGICAL AND SURGICAL PATHOLOGY (Лучшие интеллектуальные исследования, 2024)
Abstract.  The problem of surgical treatment of combined diseases of the abdominal organs has long attracted the attention of specialists in various fields. The combination of diseases of the abdominal organs and female genital organs is quite common and, according to various authors, ranges from 2.8 to 63%, in particular, diseases of the appendix accompany gynecological pathology in 3.1 - 3.3%, gallbladder - in 3.1 - 15% [4,6,7,8]. Simultaneous surgery is the simultaneous performance of two or more independent operations for various diseases for which surgical treatment is indicated [5].